Influence of orotracheal intubation on preterm infant palate shape between 12 and 24 months old - Costa, Soraya Carvalho da; Santos, Maria Teresa Botti Rodrigues dos; Carvalho, Werther Brunow de; Miyazato, Denize Gomes; Ceccon, Maria Esther Jurfest Rivero; Diniz, Edna Maria de Albuquerque (Journal of Oral Diagnosis, 2017)
Introduction: Mechanical ventilation (MV) is indicated in diverse clinical situations in which the individual develops acute or chronic respiratory failure. Objective: To eva- luate the palate shape of preterm infants aged 12 to 24 months who were submitted to orotracheal intubation (OTI) and mechanical ventilation. Methods: This cross-sectional observational study included preterm infants submitted to MV by OTI for at least seven days, who weighed less than 2000 g at birth, and were attended at the Preterm Infant Care Outpatient Clinic of the University Hospital of the University of São Paulo and the Premature Infant Outpatient Clinic of the Children’s Institute of the Clinics Hospital of the School of Medicine of the University of São Paulo. Sociodemographic data were collected from neonatal medical records of the participating children. The oral cavity was examined to classify palate shape into square, narrow or ovoid. Statistical analyses were performed using the ANOVA F, Kruskal-Wallis and Chi-square tests, with a 5% significance level. Results: The mean period of OTI was 25.3 ± 25.8 days, and the children presented a significantly higher percentage of narrow shaped palate (p<0.001). Conclusion: The palate in preterm infants submitted to invasive MV by OTI is predominantly narrow and deep.